Placental Growth Factor, Soluble fms-Like Tyrosine Kinase 1, Soluble Endoglin, IL-6, and IL-16 as Biomarkers in Preeclampsia - Carmen Rădulescu; Anca Bacârea; Adina Huțanu; Rozalia Gabor; Minodora Dobreanu (Mediators of Inflammation)
Preeclampsia (PE), an important cause of maternal and perinatal morbidity and mortality worldwide, is a pregnancy-related disease characterized by hypertension and proteinuria after 20 weeks of gestation. The aim of our study was to find a practical panel of biomarkers useful in early diagnosis of PE. This study was carried out at the Obstetrics and Gynecology Department in Tîrgu Mureș University Hospital, Romania, between January 2014 and July 2015 and included 68 pregnant women (47 preeclamptic women and 21 controls) with gestational age between 16 and 20 weeks at enrollment. The biomarkers PlGF, sFlt-1, sEng, IL-6, and IL-16 were determined by ELISA test. We compared the serum levels of soluble markers analysed in preeclamptic women and controls during the second and third trimesters of pregnancy and we found that the best predictor for PE was PlGF with a sensitivity of 100% at a concentration threshold of 120.16 pg/mL, a diagnosis accuracy of 70.8%, and AUC of 0.684 (p=0.005). We also estimated the risk for PE according to BMI and we found that pregnant women with weight >90 kg had 7 times higher risk for PE. Second-trimester PlGF serum level may serve as an early biomarker for the diagnosis of PE.